Optimizing Bi2O3 and TiO2 to achieve the maximum non-linear electrical property of ZnO low voltage varistor - Abdollahi, Yadollah; Zakaria, Azmi; Aziz, Raba'ah Syahidah; Ahmad Tamili, Siti Norazilah; Matori, Khamirul Amin; Mohd Shahrani, Nuraine Mariana; Mohd Sidek, Nurhidayati; Dorraj, Masoumeh; Moosavi, Seyedehmaryam (Chemistry Central, 2013)
In fabrication of ZnO-based low voltage varistor, Bi2O3 and TiO2 have been used as former and grain growth enhancer factors respectively. Therefore, the molar ratio of the factors is quit important in the fabrication. In this paper, modeling and optimization of Bi2O3 and TiO2 was carried out by response surface methodology to achieve maximized electrical properties. The fabrication was planned by central composite design using two variables and one response. To obtain actual responses, the design was performed in laboratory by the conventional methods of ceramics fabrication. The actual responses were fitted into a valid second order algebraic polynomial equation. Then the quadratic model was suggested by response surface methodology. The model was validated by analysis of variance which provided several evidences such as high F-value (153.6), very low P-value (<0.0001), adjusted R-squared (0.985) and predicted R-squared (0.947). Moreover, the lack of fit was not significant which means the model was significant.